GEOGRAPHIES OF URBAN MINING IN THE GLOBAL SOUTH - Lopes dos Santos, Kaue; Jacobi, Pedro Roberto (Mercator; Vol 20 (2021), 2021)
The collection, recycling and sale of waste electrical and electronic equipment (WEEE) – or e-waste – are part of the so-called "urban mining" and have been occurring according to different technical-normative conditions, which impact the environment, society and the economy in different ways, especially in the urban spaces of the Global South. This article establishes a comparative analysis of urban mining in the Sao Paulo Macrometropolis (Brazil) and the Greater Accra Region (Ghana) through exploratory qualitative research. The results reveal a broad spectrum of actor-network arrangements established in the universe of e-waste, also confirming the relevance of political economy for understanding the technical and regulatory aspects of recycling in different geographical contexts. Keywords : WEEE; Recycling; Collect; Commercialization; Comparative Urban Study.